Polyurethane elastomer, and polyurethane molding
By designing the specific structure of the matrix and domain in polyester rubber, the problem of difficulty in achieving low compression coefficient and high wear resistance at the same time in the prior art is solved, and the flexibility, low compression coefficient and high wear resistance of the polyester rubber material are achieved.
Patent Information
- Application Number
- JP2023171456
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-02
- Publication Date
- 2025-04-14
AI Technical Summary
The prior art is difficult to achieve a low compression coefficient of polyester rubber material while maintaining high wear resistance.
By introducing a structure with a matrix and multiple domains into the polyester rubber, specifically, the relationship between the elastic properties of the domain and the elastic properties of the matrix is A
The flexibility, low compression coefficient and high wear resistance of polyester rubber materials are achieved, which are specifically manifested as low wear rate and rapid retraction performance under specific conditions.
Smart Images

Figure 2025062409000009 
Figure 2025062409000010 
Figure 2025062409000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a polyurethane elastomer and a polyurethane molded article. [Background technology]
[0002] Polyurethane elastomers are used in a wide range of applications, including artificial leather, synthetic leather, paints, coating agents, adhesives, etc. In general, polyurethane elastomers are made from the reaction product of polyisocyanate and polyol, and are composed of hard segments derived from the polyisocyanate and soft segments derived from the polyol. Polyols, which are one of the raw materials for polyurethane elastomers, are classified into polyether polyols, polyester polyols, polycarbonate polyols, etc., depending on the difference in molecular chain structure, and the type of polyol is selected according to the required performance. Among them, polyurethane elastomers having a polycarbonate structure made from polycarbonate polyols have excellent abrasion resistance. In addition, they are known to be superior in heat resistance, weather resistance, hydrolysis resistance, etc., compared to polyurethane elastomers having a polyether structure or polyester structure.
[0003] On the other hand, in polyurethane elastomers having a polycarbonate structure, strong intermolecular forces act between the polycarbonate structures, causing a significant increase in hardness of the polyurethane elastomer, making it difficult to apply the polyurethane elastomer having a polycarbonate structure to applications requiring low hardness.
[0004] A typical example of a low-hardness elastomer is a silicone elastomer, which is superior in compression set to polyurethane elastomers having a polycarbonate structure, but is inferior in abrasion resistance. In light of this, there is a demand for elastomers that have excellent abrasion resistance similar to that of polyurethane elastomers having a polycarbonate structure, and have a low compression set comparable to that of silicone elastomers.
[0005] Patent Document 1 discloses a polyurethane elastomer including a structural unit derived from a polyol, a structural unit derived from a polyether carbonate diol having a specific structure, and a structure derived from a polycarbonate diol having two repeating units having a specific structure and / or a polyalkylene ether glycol having two repeating units having a specific structure. Patent Document 2 discloses a developing blade for an electrophotographic device, which is formed by adhering a blade member to a support, and discloses that the material of the blade member is a polyurethane elastomer which is a reaction product of a polyol compound and a polyisocyanate compound, and that the polyol compound is a blend of polydimethylsiloxane having active hydrogen at least at both ends of the molecule and polypropylene glycol. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2020-128461 A [Patent Document 2] JP 2000-29307 A Summary of the Invention [Problem to be solved by the invention]
[0007] According to the study by the present inventors, the polyurethane elastomer according to Patent Document 1 has a higher viscosity than conventional polyurethanes. Although it has excellent flexibility compared to recarbonate polyurethane, it is difficult to realize a low hardness comparable to that of silicone elastomer. In addition, the polyurethane elastomer according to Patent Document 1 has difficulty in realizing good friction properties comparable to those of general polycarbonate polyurethane, probably because the polyether segments are uniformly present in the polyurethane elastomer. In addition, the polyurethane elastomer according to Patent Document 2 is excellent in terms of hardness and friction properties, but it is difficult to realize a low compression set comparable to that of silicone elastomer.
[0008] At least one aspect of the present disclosure is directed to providing a polyurethane elastomer that provides a molded article that is flexible yet has a small compression set and high abrasion resistance. At least one aspect of the present disclosure is directed to providing a polyurethane elastomer molded article that is flexible, yet has a small compression set and is resistant to wear. [Means for solving the problem]
[0009] According to at least one aspect of the present disclosure, there is provided a polyurethane elastomer having a matrix and a plurality of domains dispersed in the matrix, wherein, in a viscoelastic image obtained by a scanning probe microscope of a cross-sectional plane parallel to one surface of a first molded body having a cubic shape with a side length of 100 μm and made of the polyurethane elastomer, a parameter A indicating a viscoelastic term of the domain and a parameter B indicating a viscoelastic term of the matrix satisfy A < B; the micro rubber hardness of a second molded body made of the polyurethane elastomer at a temperature of 23°C is 20 to 50 degrees; and in an indentation test using a nanoindenter at 23°C on the second molded body, when a Vickers indenter is pressed into the second molded body at a loading rate of 10 mN / 30 seconds, maintained at a load of 10 mN for 60 seconds, and then unloaded, the strain after 5 seconds of unloading is 1.0 μm or less. There is provided a polyurethane elastomer in which the mass reduction rate of a wear test piece having a sheet shape with a length of 30 mm, a width of 30 mm, and a thickness of 2 mm and made of the polyurethane elastomer is 10.0 mass% or less when a ball-on-disk wear test is performed according to the following conditions (1) to (6) in accordance with JIS R1613:2010. (1) Ball Material: Stainless steel Diameter: 10 mm (2) Load: 100 g (3) Environment: Temperature 23°C, 50% RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the test piece is placed: 300 rpm.
[0010] According to at least one aspect of the present disclosure, there is provided a molded body including the above-described polyurethane elastomer.
Advantages of the Invention
[0011] According to at least one aspect of the present disclosure, it is possible to obtain a polyurethane elastomer that provides a polyurethane elastomer molded article that is flexible, has small compression set, and exhibits high abrasion resistance. Also, according to at least one aspect of the present disclosure, it is possible to obtain a molded article that is flexible, has small compression set, and exhibits high abrasion resistance. [Brief description of the drawings]
[0012] [Figure 1] 4A to 4C are explanatory diagrams illustrating deformation of a urethane elastomer according to the present disclosure. [Diagram 2] FIG. 1 is a schematic diagram illustrating a method for producing a urethane elastomer according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In this specification, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in this disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.
[0014] The present inventors have conducted extensive research to obtain a polyurethane elastomer that is flexible, has a small compression set, and is excellent in abrasion resistance. As a result, they have found that a polyurethane elastomer that satisfies the following requirements (1-1) to (1-5) contributes to achieving the above object.
[0015] Requirement (1-1): The material has a matrix domain structure having a matrix and a plurality of domains dispersed in the matrix. Requirement (1-2): The relationship between parameter A indicating the viscoelasticity term of the domain and parameter B indicating the viscoelasticity term of the matrix, which is measured in a viscoelastic image of a cross section parallel to one face of a first molded body having a cubic shape with a side length of 100 μm and made of a polyurethane elastomer, by a scanning probe microscope, is A <Bである。 That is, in a cut section parallel to one surface of the first molded article, a matrix domain structure of the polyurethane elastomer is observed, and the elastic modulus of the matrix of the polyurethane elastomer observed in the cross section is greater than the elastic modulus of the domain.
[0016] Requirement (1-3): The micro rubber hardness of the second molded body having a cubic shape with one side measuring 2 mm is 20 to 50 degrees at a temperature of 23°C. Requirement (1-4): In an indentation test using a nanoindenter at 23°C on a cubic second compact with sides of 2 mm, a Vickers indenter is pressed into the second compact at a loading rate of 10 mN / 30 seconds, the load of 10 mN is maintained for 60 seconds, and then the load is released. The distortion 5 seconds after the load is released is 1.0 μm or less. Requirement (1-5): When a ball-on-disk abrasion test is performed on the surface of a polyurethane elastomer sheet-shaped piece measuring 30 mm in length, 30 mm in width, and 2 mm in thickness under the following conditions (1) to (6) in accordance with JIS R1613:2010, the mass loss of the abrasion test piece is 10.0% by mass or less. (1) Ball Material: Stainless steel, Diameter: 10mm (2) Load: 100g (3)Environment: Temperature 23℃, 50%RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the test specimen is placed: 300 rpm.
[0017] In polyurethane elastomers, the matrix is responsible for the function of recovery from deformation, and the domain is responsible for reducing the hardness of the polyurethane elastomer. Such polyurethane elastomers exhibit softness and quick recovery from deformation. On the other hand, general polyurethane elastomers also have a difference in elastic modulus between the so-called hard segment and soft segment. However, in general urethane elastomers, the soft segment constitutes the matrix and the hard segment constitutes the domain. It is believed that there has not been a polyurethane elastomer that exhibits the fast recovery rate from deformation required by requirement (1-4) while having the flexibility required by requirement (1-3). Furthermore, it is believed that no polyurethane elastomer has existed that also satisfies the high abrasion resistance required in the above requirement (1-5).
[0018] FIG. 1A is a cross-sectional view of a molded article 3 containing a polyurethane elastomer according to one embodiment of the present disclosure. FIG. 1A shows a schematic diagram of a matrix 31 of a polyurethane elastomer and a plurality of domains 32 dispersed in the matrix 31, as observed on a cross section parallel to one surface of a molded article. As described above, the polyurethane elastomer has a matrix 31 and domains 32 dispersed in the matrix. That is, the polyurethane elastomer has a matrix-domain structure. The matrix exhibits higher elasticity than the domains.
[0019] 1A and 1B are explanatory diagrams of the deformation recovery of a polyurethane molded body 3 according to one embodiment of the present disclosure. As shown in FIG. 1A, a plurality of domains 32 are dispersed in a matrix 31. Since the domains 32 have a lower elasticity than the matrix 31, when the polyurethane molded body 3 is compressed in the direction of the arrow F as shown in FIG. 1B, the domains 32 deform preferentially. Therefore, even if the matrix 31 has a high elasticity, the micro rubber hardness of the polyurethane molded body can be reduced. Furthermore, when the polyurethane molded body is released from compression, the elasticity of the matrix 31, which is the continuous phase, allows the thickness of the molded body to quickly return to the thickness before compression.
[0020] (Number of domains N) In the first molded article made of the polyurethane elastomer and having a cubic shape with one side of 100 μm, the number N of the domains contained in the first molded article can be 10 to 77,000. The number N of the domains can be 100 to 77,000, or even 700 to 77,000. When the number N of the domains is within the above range, a polyurethane elastomer that is flexible yet has small compression deformation distortion can be easily obtained. The number N of the domains can be adjusted by the mixing conditions (shear force and time) during preparation of the urethane prepolymer and the molecular weight and amount of the polyol and polyisocyanate added. The number of domains N can be determined by three-dimensional measurement of the first molded body using FIB-SEM. The first molded body may be a heat-cured polyurethane elastomer as is, or the heat-cured polyurethane elastomer may be processed into a predetermined shape using a microtome to obtain the first molded body.
[0021] FIB-SEM is a technique in which a sample is processed using a FIB (Focused Ion Beam) device, and the exposed cross section of the sample is observed using a SEM (scanning electron microscope). To examine the three-dimensional structure, a large number of photographs are taken by repeating successive processing and observations, and then these SEM images are subjected to 3D reconstruction processing using computer software. The three-dimensional structure of the sample can then be examined by constructing a three-dimensional image of the sample. As a specific method for measuring the number N of domains, a FIB-SEM (manufactured by FEI) is used to obtain three-dimensional stereoscopic images of the first molded body at intervals of 60 nm. Then, the number N of domains is calculated for the obtained images using 3D visualization and analysis software Avizo (registered trademark, manufactured by FEI). A more specific measurement method will be described later.
[0022] (Arithmetic mean value of the equivalent spherical diameter of the domain Da) In the first molded body made of the polyurethane elastomer and having a cubic shape with a side length of 100 μm, the arithmetic mean value Da of the sphere-equivalent diameter of the domains may be 1.0 to 30.0 μm. The arithmetic mean value Da may be 2.0 to 20.0 μm, or 2.0 to 15.0 μm. When the arithmetic mean value Da is in the above range, a polyurethane elastomer that is flexible but has a small compression deformation strain is easily obtained. The arithmetic mean value Da can be adjusted by the mixing conditions (shear force and time) during preparation of the urethane prepolymer, and the molecular weight and amount of the polyol and polyisocyanate added. The arithmetic mean value Da can be determined by three-dimensional measurement of the first molded body using the above-mentioned FIB-SEM. A specific measurement method will be described later.
[0023] (Proportion V of the total volume of the domain in the first compact) In the first molded body having a cubic shape with a side length of 100 μm and made of the polyurethane elastomer, the ratio V of the total volume of the domains in the first molded body may be 15 to 45% by volume. Further, the ratio V of the total volume of the domains in the first molded body may be 20 to 45% by volume, may be 25 to 42% by volume, and preferably is 25 to 41% by volume. When the ratio V of the total volume of the domains in the first molded body is within the above range, it is easy to obtain a polyurethane elastomer that is flexible and has a small compression deformation strain. Further, the ratio V of the total volume of the domains in the first molded body can be adjusted by the mixing conditions (shearing force and time) during the production of the urethane prepolymer and the molecular weight and addition amount of the polyol and polyisocyanate. The ratio of the total volume of the domains in the first molded body can be determined by three-dimensional measurement of the first molded body using the above-described FIB-SEM. Specific measurement methods will be described later.
[0024] (Parameter indicating viscoelastic term) In the first molded body having a cubic shape with a side length of 100 μm and made of the polyurethane elastomer, in the viscoelastic image of a cut surface parallel to one surface of the first molded body measured by a scanning probe microscope, a parameter A indicating the viscoelastic term of the domain and a parameter B indicating the viscoelastic term of the matrix satisfy A < B. That is, the elastic modulus of the matrix of the polyurethane elastomer observed on the cut surface is larger than the elastic modulus of the domain. Thereby, it becomes easy to achieve both hardness and deformation recovery. The difference in the relative elastic modulus between the matrix 31 and the domain 32 can be determined by thinning the first molded body and measuring it with a scanning probe microscope (SPM / AFM). As the scanning probe microscope, for example, "S-Image" (trade name) manufactured by Hitachi High-Technologies Corporation can be used. Further, as means for thinning, for example, a sharp razor, a microtome, a focused ion beam method (FIB), etc. can be mentioned, but in the present disclosure, a microtome is used. The slice is prepared from an arbitrary cut surface parallel to one face of the first molded body having a cubic shape with one side of 100 μm, and the observation region of the viscoelastic image on the cut surface is an arbitrary 50 μm square region.
[0025] The measurement mode for the viscoelastic image using SPM is the micro-viscoelastic dynamic force mode (VE-DFM). The cantilever used is a silicon micro-cantilever for DMF ("SI-DF3" (product name), Hitachi High-Tech Science Corporation, spring constant = 1.9 N / m). The scanning frequency is 0.5 Hz. VE-DFM is one of the measurement modes of SPM (scanning probe microscope). In VE-DFM, a surface topography image can be obtained by controlling the distance between the probe and the measurement sample so that the vibration and amplitude of the cantilever are constant while the cantilever is resonating.
[0026] After acquiring a viscoelastic image, the parameters indicating the viscoelastic term in each observation region are obtained for 10 points each for the matrix and domain, and their arithmetic mean values are taken as parameter A indicating the viscoelastic term of the domain and parameter B indicating the viscoelastic term of the matrix. Note that the units of parameters A and B are mV, and the larger the value, the higher the elasticity.
[0027] The ratio (A / B) of parameter A to parameter B is preferably 0.65 or less, may be 0.50 or less, or may be 0.40 or less. The smaller A / B is, the greater the difference in viscoelasticity between the matrix and the domain, making it easier to achieve both hardness and recovery from deformation. There is no particular limit to the lower limit of A / B, but the smaller the value, the more preferable. Specifically, for example, it is 0.10. For example, A / B is preferably 0.10 to 0.65, 0.10 to 0.50, or 0.10 to 0.40. The parameters A and B can be adjusted, for example, by changing the elastic modulus of the domain and the matrix. The elastic modulus of the matrix can be adjusted by the molecular weight, bonding species, and added amount of the polyol or polyisocyanate. The elastic modulus of the domain can be adjusted by the molecular weight, bonding species, and added amount of the polyol or polyisocyanate, or by adding a chain extender such as a polyhydric alcohol. The value of parameter A is not particularly limited, but may be, for example, 50 to 120 mV, or 60 to 110 mV. The value of parameter B is not particularly limited, but may be, for example, 190 to 310 mV, or 210 to 290 mV.
[0028] (Micro rubber hardness of molded body) The second molded body made of polyurethane elastomer has a micro rubber hardness of 20 to 50 degrees at a temperature of 23°C. Here, the second molded body is a cubic molded body with one side of 2 mm. If the thickness of the sample is less than 2 mm, the second molded body is stacked in the thickness direction to form a cubic second molded body with one side of 2 mm. By having a micro rubber hardness of 50 degrees or less, flexibility is good and hardness is low. By having a micro rubber hardness of 20 degrees or more, mechanical strength is high and abrasion resistance is good. The micro rubber hardness is preferably 25 to 50 degrees, and more preferably 30 to 50 degrees. The micro rubber hardness can be adjusted by the elastic modulus of the matrix, the ratio of the matrix to the domain, etc. Specifically, for example, increasing the elastic modulus of the matrix acts in the direction of increasing the micro rubber hardness. The micro rubber hardness is determined as follows. The measurement point is the approximate center of any one face of the cubic second molded body with a side length of 2 mm, and the micro rubber hardness is measured at a temperature of 23°C using a micro rubber hardness meter (product name: MD-1capa; manufactured by Kobunshi Keiki Co., Ltd., indenter: type A (cylindrical, diameter 0.16 mm, height 0.5 mm, outer diameter 4 mm, inner diameter 1.5 mm), measurement mode: peak hold mode). When the thickness of the sample is less than 2 mm, the measurement point is the approximate center of one face of the second molded body that can measure the micro rubber hardness from the thickness direction of the sample of the second molded body. Moreover, the heat-cured polyurethane elastomer may be used as it is for the second molded body, or the heat-cured polyurethane elastomer may be processed into a predetermined shape using scissors to form the second molded body.
[0029] (Recovery from deformation) In an indentation test using a nanoindenter at a temperature of 23°C of a second molded article made of a polyurethane elastomer, a Vickers indenter is pressed into the second molded article at a loading rate of 10 mN / 30 seconds, and the load of 10 mN is maintained for 60 seconds, after which the load is released. The strain 5 seconds after the load is released is 1.0 μm or less. The strain 5 seconds after the load is released is preferably 0.8 μm or less, more preferably 0.7 μm or less, and even more preferably 0.6 μm or less. The lower limit of the strain 5 seconds after the load is released is not particularly limited, but is usually 0.0 μm, and may be 0.1 μm. For example, it is preferably 0.0 to 1.0 μm, 0.0 to 0.8 μm, 0.0 0.1 to 0.6 μm. By setting the strain 5 seconds after unloading within the above range, a polyurethane elastomer exhibits a fast recovery rate from deformation. The strain 5 seconds after unloading can be adjusted mainly by the degree of crosslinking of the polyurethane constituting the matrix, that is, by selecting the type of polyol or isocyanate compound used as the raw material for the polyurethane.
[0030] The value of the strain 5 seconds after unloading is obtained as follows. The measurement point is approximately the center of any one face of the cubic second compact with a side length of 2 mm, and a pressing test is performed at a temperature of 23°C using a nanoindenter (product name: Fischerscope HM2000, manufactured by Fisher Instruments Co., Ltd., a Vickers indenter with a square pyramid shape and a facing angle of 136°). The Vickers indenter is pressed into the second compact at a loading rate of 10 mN / 30 seconds, and the load of 10 mN is maintained for 60 seconds. Thereafter, the load is removed at a loading rate of 10 mN / 30 seconds, and the value of the strain 5 seconds after unloading is measured. Moreover, the heat-cured polyurethane elastomer may be used as it is for the second molded body, or the heat-cured polyurethane elastomer may be processed into a predetermined shape using scissors to form the second molded body.
[0031] (Wear resistance) When a ball-on-disk abrasion test is performed on the surface in the thickness direction of a sheet-like abrasion test piece made of polyurethane elastomer, measuring 30 mm in length, 30 mm in width, and 2 mm in thickness, in accordance with JIS R1613:2010 under the following conditions (1) to (6), the mass loss rate of the abrasion test piece is 10.0 mass% or less. In addition, the mass loss rate is preferably 5.0 mass% or less, more preferably 3.1 mass% or less, even more preferably 1.6 mass% or less, and particularly preferably 0.5 mass% or less. By being in the above range, good abrasion resistance is obtained.
[0032] (1) Ball Material: Stainless steel Diameter: 10mm (2) Load: 100g (3)Environment: Temperature 23℃, 50%RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the test specimen is placed: 300 rpm.
[0033] The wear test is carried out as follows. First, the mass of the wear test piece is measured. Next, the wear test piece is fixed with double-sided tape so that the center of the wear test piece is located approximately at the center of the sliding disk of a ball-on-disk friction wear tester (product name: HEIDON Type: 20, manufactured by Shinto Chemical Co., Ltd.). At this time, the surface in the thickness direction of the wear test piece is arranged so as to be in contact with the sliding disk. Next, the indenter made of the above-mentioned ball is pressed against the center of the wear test piece with a load of 100 g, and the wear test piece is rotated and slid for 60 minutes with a sliding circle diameter of 10 mm and a rotation speed of 300 rpm. After 60 minutes, the test piece is stopped, the wear powder and the double-sided tape are removed, and the mass of the test piece is measured. The mass reduction rate (mass%) is calculated from the mass of the test piece before and after the wear test. Here, the surface in the thickness direction of the wear test piece refers to a 30 mm square surface of the wear test piece, which is 30 mm long and 30 mm wide. The mass loss rate of the wear test piece can be adjusted by the type of resin in the matrix, the number of domains, the size of the domains, the type of material constituting the domains, and the like.
[0034] (Polyurethane elastomer material) The polyurethane elastomer material will be explained. The elastomer has a matrix 31 and a plurality of domains 32 dispersed in the matrix. That is, the urethane elastomer has a matrix-domain structure. It is preferable that the matrix 31 has a structure capable of increasing the deformation recovery speed and improving the abrasion resistance, and the domain 32 has a structure that contributes to suppressing an increase in micro rubber hardness.
[0035] Such a polyurethane elastomer matrix 31 preferably has a first structure (polycarbonate structure) represented by formula (1). The matrix has at least one polycarbonate structure represented by formula (1), and preferably has a plurality of polycarbonate structures. When the matrix has a plurality of polycarbonate structures represented by formula (1), the polycarbonate structures can be repeating structural units. In addition, R in the first structure represented by formula (1) 1The alkylene group having 3 to 9 carbon atoms represented by the following formula may have a linear structure or a branched structure, but more preferably has a branched structure. [ka] (In formula (1), R 1 represents an alkylene group having 3 to 9 carbon atoms (preferably 6 to 9).
[0036] Polyurethane obtained by reacting a polyol having a polycarbonate structure (polycarbonate polyol) with a polyisocyanate exhibits high elasticity and high abrasion resistance due to the strong intermolecular forces between carbonate groups, and is therefore preferable as a component of the matrix 31. Also, R 1 is an alkylene group having 3 to 9 carbon atoms, incompatibility with the domain containing the second structure (polyether structure) represented by the following formula (2) described later is ensured, and the matrix and the domain can be clearly phase-separated. This makes it possible to more reliably exhibit the two functions of the polyurethane elastomer, namely softness and fast recovery from deformation. Also, R 1 When is an alkylene group having a branched structure and having 3 to 9 carbon atoms, the intermolecular force between the carbonate groups can be appropriately suppressed, and the matrix can be prevented from becoming excessively high in elasticity.
[0037] R 1 For example, -(CH2) m -(m=3 to 9, preferably 6 to 9), -CH2C(CH3)2CH2-, -CH2CH(CH3)CH2-, -(CH2)2CH(CH3)(CH2)2-, etc. These can be used alone or in combination of two or more.
[0038] The number average molecular weight of the polycarbonate and the polyols described below can be calculated by the following formula using the hydroxyl value (mgKOH / g) and valence. For example, the number average molecular weight of a polyether polyol with a hydroxyl value of 56.1 mgKOH / g and a valence of 2 can be calculated to be 2000. Number average molecular weight = 56.1 x 1000 x valence ÷ hydroxyl value
[0039] The elastic modulus of the matrix can be adjusted by, for example, increasing the crosslink density using a trimer compound or polymer compound of polyisocyanate. Normally, increasing the elastic modulus also increases the micro rubber hardness of the polyurethane elastomer. Since multiple low elasticity domains are dispersed in the hardened steel, excessive hardness can be prevented.
[0040] The domain 32 preferably contains a second structure (polyether structure) represented by formula (2). The domain has at least one polyether structure represented by formula (2), and preferably has a plurality of polyether structures represented by formula (2). When the domain has a plurality of polyether structures represented by formula (2), the polyether structures can be repeating structural units. In addition, R in the structural unit represented by formula (2) 2 The alkylene group having 3 to 6 carbon atoms represented by the following formula may have a linear structure or a branched structure, but more preferably has a branched structure. [ka] (In formula (2), R 2 represents an alkylene group having 3 to 6 carbon atoms (preferably 3 to 4).
[0041] Polyethers exhibit low elastic modulus due to weak intermolecular forces between ether groups, making them a preferred component of domains. Also, R 2is an alkylene group having 3 to 6 carbon atoms, which ensures incompatibility with the matrix having the polycarbonate structure represented by formula (1) and results in clear phase separation between the matrix and the domain, which is preferable.
[0042] R 2 For example, -(CH2) m -(m=3 to 6), -CH2CH(CH3)-, -CH2C(CH3)2CH2-, -CH2CH(CH3)CH2-, -(CH2)2CH(CH3)CH2-, etc. These can be used alone or in combination of two or more.
[0043] The number average molecular weight of the polyether structure represented by formula (2) is preferably 1000 to 50000. More preferably, it is 1200 to 30000. When the number average molecular weight is 1000 or more, the incompatibility between the domain and the matrix containing the polycarbonate structure represented by formula (1) becomes better, and the phase separation between the matrix and the domain becomes clear, which is preferable. Also, when the number average molecular weight is 50000 or less, the domain is easily formed, and the phase separation form is stabilized, which is preferable.
[0044] The chemical structures of the matrix and domains can be analyzed using, for example, a spectroscopic analyzer such as an AFM infrared spectroscopic analyzer, a microscopic infrared spectroscopic analyzer, or a microscopic Raman spectroscopic analyzer, or a mass spectrometer.
[0045] (Method of producing polyurethane elastomer) An example of the method for producing the above-mentioned polyurethane elastomer includes a method having the following steps (i) to (iii). Step (i): A step of reacting a first polyether having at least two isocyanate groups with a first polycarbonate polyol having at least two hydroxyl groups to obtain a urethane reactive emulsifier having at least two hydroxyl groups. Step (ii): A step of obtaining a dispersion in which droplets containing at least a portion of the urethane reactive emulsifier are dispersed in the second polycarbonate polyol. Step (iii): preparing a mixture for forming a polyurethane elastomer containing the dispersion obtained in step (ii) and a polyisocyanate having at least two isocyanate groups, and then reacting the urethane reactive emulsifier, the second polycarbonate polyol, and the polyisocyanate in the mixture for forming a polyurethane elastomer.
[0046] Each step of the above manufacturing method will be described with reference to FIG. In step (i), a first polyether 51 having at least two isocyanate groups is mixed with a first polycarbonate polyol 52 having at least two hydroxyl groups. In the presence of a catalyst, the isocyanate groups and hydroxyl groups in the mixture are reacted to link them via a urethane bond, thereby obtaining a urethane reactive emulsifier 53 having at least two hydroxyl groups. The urethane reactive emulsifier is a reactive emulsifier having a urethane bond.
[0047] In step (ii), the urethane reactive emulsifier 53 obtained in step (i) is dispersed in the second polycarbonate polyol 55. The segment derived from the first polyether 51 contained in the urethane reactive emulsifier 53 is not compatible with the second polycarbonate polyol 55 and forms droplets 54. On the other hand, in the second polycarbonate polyol 55, the droplets 54 containing the segment derived from the first polyether constituting a part of the urethane reactive emulsifier are uniformly and stably dispersed via the segment derived from the first polycarbonate polyol 52 contained in the urethane reactive emulsifier 53. As a result, a dispersion is obtained in which the droplets 54 containing the segment derived from the first polyether 51 of the urethane reactive emulsifier 53 are dispersed in the second polycarbonate polyol 55. Note that, for the sake of explanation, steps (i) and (ii) are described separately, but these steps may be a continuous series of steps.
[0048] In step (ii), the second polycarbonate polyol 55 in which the droplets 54 are dispersed can be the unreacted product of the first polycarbonate polyol used in step (i) with the first polyether. That is, in step (i), by using an excess amount of the first polycarbonate polyol relative to the first polyether, a dispersion in which the urethane reactive emulsifier 53 described in step (ii) is dispersed in the excess first polycarbonate polyol, i.e., the second polycarbonate polyol 55, can be obtained. Even when an excess amount of the first polycarbonate polyol is used, a polycarbonate polyol (second polycarbonate polyol) as a dispersion medium for the urethane reactive emulsifier can be additionally added. In this case, the polycarbonate polyol to be added may have the same chemical composition as the first polycarbonate polyol used in step (i) or may be different.
[0049] On the other hand, in step (i), the first polycarbonate polyol and the first polyether are reacted in equivalent amounts, and when the first polycarbonate polyol is completely consumed, a new polycarbonate polyol is used as the second polycarbonate polyol to prepare a dispersion in step (ii). Even in this case, the polycarbonate polyol used as the second polycarbonate polyol may have the same chemical composition as the first polycarbonate polyol or may have a different chemical composition.
[0050] Finally, in step (iii), a polyurethane elastomer forming mixture is prepared, which contains the dispersion prepared in step (ii) and a polyisocyanate 56 having at least two isocyanate groups. Next, the terminal hydroxyl groups of the urethane reactive emulsifier 53, the hydroxyl groups of the second polycarbonate polyol 55, and the isocyanate groups of the polyisocyanate 56 in the polyurethane elastomer forming mixture are reacted. In this way, a network structure is formed via urethane bonds, and the polyurethane elastomer forming mixture is cured to obtain a polyurethane elastomer. The polyurethane elastomer 500 thus obtained has a matrix domain structure in which domains 32 containing a polyether derived from the first polyether 51 are dispersed in a matrix 31 containing a urethane elastomer having a polycarbonate derived from the first polycarbonate polyol 52 and the second polycarbonate polyol 55. The domains 32 are mainly In the polyurethane elastomer, the domain is constituted by a polyether structure, and a component having substantially no crosslinked structure, i.e., a liquid component, may exist inside the domain. This allows the domain to have a low elastic modulus.
[0051] Furthermore, it is believed that the domain is not simply a liquid component confined in the matrix, but that the domain and the matrix are chemically bonded to each other through urethane bonds at the boundary between the domain and the matrix, and therefore the recovery of the domain from deformation when the load applied to the polyurethane elastomer is removed can be linked to the recovery of the matrix from deformation. Here, as described above, the substantially liquid domain does not substantially have a crosslinked structure inside. Therefore, it is difficult for the domain that is deformed by the application of a load to the polyurethane elastomer to autonomously recover from the deformation. However, in the polyurethane elastomer, it is considered that the domain is chemically bonded to the matrix at the boundary portion with the matrix. This allows the domain to recover from the deformation together with the recovery of the deformation of the matrix. This achieves stable deformation (amount of deformation) and stable recovery from the deformation even when the polyurethane elastomer is repeatedly subjected to loading and unloading.
[0052] The above steps (i) to (ii) are steps for stably dispersing a polyether, which is originally difficult to disperse stably and uniformly due to its low compatibility, in a polyol. That is, the first polyether 51 is reacted with the first polycarbonate polyol 52 to obtain a urethane reactive emulsifier 53. This is a step for obtaining a dispersion in which the polyether segments derived from the first polyether 51 are stably and uniformly dispersed in the second polycarbonate polyol. This makes it easy to prepare a polyurethane elastomer in which domains 32 having a high circularity and a relatively uniform size distribution, which are small on the order of micrometers, are dispersed in the matrix 31.
[0053] As another method for mixing materials with low compatibility, for example, there is a method of mixing and dispersing them with high shear force. However, in this method, high shear force is applied to the polyether, which results in distorted domain shapes and reduced circularity, and the sizes of the domains may also be non-uniform. In addition, the dispersion state is unstable, and aggregation of the domains progresses over a relatively long period of time. In addition, the incompatibility of the polyether and the polycarbonate polyol is not guaranteed, and the phase separation between the matrix and domains of the resulting polyurethane elastomer becomes unclear. Therefore, it is difficult to obtain a polyurethane elastomer that provides an elastic body that is flexible and has excellent deformation recovery properties, as disclosed herein.
[0054] The first polyether has at least two isocyanate groups. The first polyether is preferably a polyether having a second structure represented by formula (2). The first polyether can be obtained, for example, by reacting a polyether polyol (corresponding to the "first polyol" in the examples) having at least two hydroxyl groups and the second structure represented by formula (2) with a polyisocyanate having at least two isocyanate groups. Examples of polyether polyols include polyether polyols containing an alkylene structure, such as polypropylene glycol, polytetramethylene glycol, a copolymer of tetrahydrofuran and neopentyl glycol, and a copolymer of tetrahydrofuran and 3-methyltetrahydrofuran, and random or block copolymers of these polyalkylene glycols. These may be used alone or in combination of two or more.
[0055] Among the polyether polyols, incompatibility with the second polycarbonate polyol, From the viewpoint of realizing low hardness, amorphous polyether polyols are preferred. More preferably, the liquid contains at least one selected from the group consisting of polypropylene glycol, a copolymer of tetrahydrofuran and neopentyl glycol, and a copolymer of tetrahydrofuran and 3-methyltetrahydrofuran.
[0056] The number average molecular weight of the polyether polyol is preferably 1000 to 50000. More preferably, it is 1200 to 30000. When the number average molecular weight is 1000 or more, the incompatibility with the polycarbonate polyol is ensured, and the phase separation between the matrix and the domain of the obtained urethane elastomer becomes clear, which is preferable. Also, when the number average molecular weight is 50000 or less, the domain is easily formed, and the phase separation form is stabilized, which is preferable.
[0057] Examples of polyisocyanates to be reacted with polyether polyol include pentamethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, trimer compounds (isocyanurates) of these polyisocyanates, polymer compounds, allophanate type polyisocyanates, biuret type polyisocyanates, water-dispersible polyisocyanates, etc. These polyisocyanates can be used alone or in combination of two or more kinds. Among the polyisocyanates, a bifunctional isocyanate having two isocyanate groups is preferred because of its high compatibility with the first polyether and the ease of adjusting physical properties such as viscosity. More preferably, the polyisocyanate contains at least one selected from hexamethylene diisocyanate, isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate. Among these, xylylene diisocyanate is even more preferred.
[0058] In the step of reacting polyether polyol with polyisocyanate, the isocyanate index is preferably in the range of 1.2 to 5.0. The isocyanate index indicates the ratio ([NCO] / [OH]) of the number of moles of isocyanate groups in an isocyanate compound to the number of moles of hydroxyl groups in a polyol compound. The first polyether obtained by the reaction of polyether polyol with polyisocyanate has a structure in which hydroxyl groups and isocyanate groups are linked via urethane bonds formed by the reaction of the hydroxyl groups and isocyanate groups. The number average molecular weight is preferably 1,000 to 50,000. More preferably, it is 1,200 to 30,000.
[0059] The first polycarbonate polyol has at least two hydroxyl groups. It is also preferable that the first polycarbonate polyol has a first structure represented by formula (1). Examples of the first polycarbonate polyol include a reaction product of a polyhydric alcohol and phosgene, and a ring-opening polymer of a cyclic carbonate ester (such as an alkylene carbonate).
[0060] Examples of polyhydric alcohols include propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene diol, 1,3-tetramethylene diol, 2-methyl-1,3-trimethylene diol, 1,5-pentamethylene diol, neopentyl glycol, 1,6-hexamethylene diol, 3-methyl-1,5-pentamethylene diol, 2,4-diethyl-1,5-pentamethylene diol, glycerin, trimethylolpropane, trimethylolethane, cyclohexanediols (such as 1,4-cyclohexanediol), and sugar alcohols (such as xylitol and sorbitol).
[0061] Examples of the alkylene carbonate include trimethylene carbonate, tetramethylene carbonate, and hexamethylene carbonate.
[0062] The number average molecular weight of the first polycarbonate polyol is preferably 500 to 10,000. More preferably, it is 700 to 8,000. When the number average molecular weight is 500 or more, the incompatibility with the domain containing the polyether of the second structural unit represented by formula (2) is ensured, and the phase separation between the matrix and the domain can be made clearer. In addition, by making the number average molecular weight 10,000 or less, an excessive increase in viscosity of the first polycarbonate polyol can be prevented.
[0063] The second polycarbonate polyol used in step (ii) may be any of the polycarbonate polyols listed in the first polycarbonate polyol. As described above, the first polycarbonate polyol and the second polycarbonate polyol may have the same chemical composition, or may be different from each other.
[0064] The polyisocyanate 56 having at least two isocyanate groups used in step (iii) may be the same as the polyisocyanates exemplified above as the raw material for the first polyether. These polyisocyanates may be used alone or in combination of two or more kinds. From the viewpoint of increasing the elastic modulus of the matrix, it is preferable that the polyisocyanate 56 includes a polyisocyanate having at least three isocyanate groups, such as a polyisocyanate trimer compound (isocyanurate) or polymer compound, an allophanate type polyisocyanate, or a biuret type polyisocyanate, among the polyisocyanates exemplified above. More preferably, the resin contains at least one selected from the group consisting of a trimer compound (isocyanurate) of pentamethylene diisocyanate, a trimer compound (isocyanurate) of hexamethylene diisocyanate, a polymeric compound of diphenylmethane diisocyanate, and polymeric MDI.
[0065] Among the above, polymeric MDI is preferred. Polymeric MDI is a mixture of monomeric MDI and high molecular weight polyisocyanate, and is represented by the following formula (A). In formula (A), n is preferably 0 or more and 4 or less. As the polymeric MDI, commercially available products may be used, and examples thereof include Millionate MR series (manufactured by Tosoh Corporation), such as Millionate MR200 (product name). [ka]
[0066] As the polyisocyanate 56 having at least two isocyanate groups, it is preferable to use a polyisocyanate having at least three isocyanate groups such as polymeric MDI in combination with a bifunctional isocyanate having two isocyanate groups. The combination of these is preferable from the viewpoint of achieving both low hardness and low compression set, since the crosslink density of the matrix can be adjusted by using these in combination.
[0067] As the catalyst, a conventionally known urethane catalyst or isocyanurate catalyst (isocyanate trimerization catalyst) can be used. These may be used alone or in combination. Examples of the urethanization catalyst include tin-based urethanization catalysts such as dibutyltin dilaurate and stannous octoate, and amine-based urethanization catalysts such as triethylenediamine, tetramethylguanidine, pentamethyldiethylenetriamine, diethylimidazole, tetramethylpropanediamine, N,N,N'-trimethylaminoethylethanolamine, 1,4-diazabicyclo[2.2.2]octane-2-methanol, and N,N-dimethylaminohexanol. These may be used alone or in combination.
[0068] Examples of isocyanurate catalysts include metal oxides such as Li2O and (Bu3Sn)2O; hydride compounds such as NaBH4; alkoxide compounds such as NaOCH3, KO-(t-Bu), and borates; amine compounds such as N(C2H5)3, N(CH3)2CH2C2H5, and 1,4-ethylenepiperazine (DABCO); alkaline carboxylate salt compounds such as HCOONa, Na2CO3, PhCOONa / DMF, CH3COOK, (CH3COO)2Ca, alkali soap, and naphthenates; alkaline formate compounds; and quaternary ammonium salt compounds such as ((R)3-NR'OH)-OCOR". In this formula, Bu represents a butyl group, Ph represents a phenyl group, and R, R', and R" represent any alkyl group. In addition, examples of the combined catalyst (cocatalyst) used as the isocyanurate catalyst include amine / epoxide, amine / carboxylic acid, amine / alkyleneimide, etc. These isocyanurate catalysts and combined catalysts may be used alone or in combination.
[0069] In the method for producing a polyurethane elastomer, a chain extender (a polyfunctional low molecular weight polyol) may be used as necessary. Examples of the chain extender include glycols having a number average molecular weight of 1000 or less. Examples of the glycol include ethylene glycol (EG), diethylene glycol (DEG), propylene glycol (PG), dipropylene glycol (DPG), 1,4-butanediol (1,4-BD), 1,6-hexanediol (1,6-HD), 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, xylylene glycol (terephthalyl alcohol), and triethylene glycol. Examples of chain extenders other than glycols include polyhydric alcohols having a valence of three or more. Examples of polyhydric alcohols having a valence of three or more include trimethylolpropane, glycerin, pentaerythritol, and sorbitol. These may be used alone or in combination. If necessary, additives such as foaming agents, microballoons, pigments, plasticizers, waterproofing agents, antioxidants, conductive agents, ultraviolet absorbing agents, and light stabilizers may also be used in combination.
[0070] The polyurethane molded article includes a polyurethane elastomer. For example, a polyurethane elastomer that has been heat-cured can be used as the polyurethane molded article as it is. The polyurethane molded article may have a foamed structure obtained by foaming using a mechanical froth method, a chemical foaming agent, or by adding microballoons. In addition, the polyurethane molded article can be applied to artificial muscles, artificial skin, synthetic leather, robot chucks, shoe soles, insoles, CMP polishing pads, stretchable electronics, flexible electronics, pressure sensors, stretch sensors, soft actuators, power generation elements, speakers, small pumps, etc. EXAMPLES
[0071] An embodiment of the present disclosure will be described in more detail below with reference to examples. However, the present disclosure is not limited to the following examples.
[0072] <Materials used> The materials used in the examples and comparative examples are listed below. [Polyol] A-1: Polyether diol (polypropylene glycol) [Product name: PREMINOL S4013F, carbon number of R2 = 3 (branched), Mn = 12,000, hydroxyl value: 9.4 mgKOH / g, manufactured by AGC] A-2: Polyether diol (polypropylene glycol) [Product name: Uniol D-2000, R2 carbon number = 3 (branched), Mn = 2,000, hydroxyl value: 55.0 mgKOH / g, NOF Corp. A-3: Polyether diol (copolymer of tetrahydrofuran and 3-methyltetrahydrofuran) [Product name: PTG-L3000, carbon number of R2 = 5 (branched) + 4 (straight chain), Mn = 2,900, hydroxyl value: 38.6 mgKOH / g, manufactured by Hodogaya Chemical Co., Ltd.] A-4: Polyether diol (polytetramethylene glycol) [Product name: PTMG2000, carbon number of R2 = 4 (straight chain), Mn = 2,000, hydroxyl value: 57.2 mgKOH / g, manufactured by Mitsubishi Chemical Corporation] A-5: Polycarbonate diol [Product name: Kuraray Polyol C-2090, carbon number of R1 = 6 (straight chain) + 6 (branched), Mn = 2,000, manufactured by Kuraray Co., Ltd.] A-6: Polycarbonate diol [Product name: Kuraray Polyol C-2065N, carbon number of R1 = 9 (straight chain) + 6 (branched), Mn = 2,000, hydroxyl value: 56.4 mg KOH / g, manufactured by Kuraray Co., Ltd.] A-7: Polycarbonate diol [Product name: Duranol T6002, carbon number of R1 = 6 (straight chain), Mn = 1,900, hydroxyl value: 57.6 mgKOH / g, manufactured by Asahi Kasei Chemical Corporation] A-8 [Product name: Duranol G3452, Mn=2.1×10 3 (Hydroxyl value: 5 3.6mgKOH / g), manufactured by Asahi Kasei Chemical Co., Ltd. A-9: Polyester diol [Product name: Kuraray Polyol P-2050, Mn=1,900, hydroxyl value: 58.1mgKOH / g, manufactured by Kuraray Co., Ltd.] [Polyisocyanate] B-1: Xylylene diisocyanate (Tokyo Chemical Industry Co., Ltd.) B-2: Polymeric MDI [Product name: Millionate MR-200, manufactured by Tosoh Corporation] B-3: Isocyanurate compound [Product name: STABIO D-370N, manufactured by Mitsui Chemicals] [Curing catalyst] C-1: 1,4-diazabicyclo[2.2.2]octane-2-methanol (product name: RZETA) [manufactured by Tosoh Corporation] [Chain extender] D-1: 1,4-butanediol
[0073] <Evaluation> The evaluation methods used in the examples and comparative examples are described below. [Evaluation 1: Confirmation of matrix domain and component analysis] A section was prepared from the polyurethane elastomer using a microtome, and a first molded body having a cubic shape with a side length of 100 μm was obtained. Then, mapping measurement was performed using a three-dimensional microscopic laser Raman spectroscopic analyzer (product name: Nanofinder 30, manufactured by Tokyo Instruments Co., Ltd.). The measurement mode was EM (Electron Multiplying), and measurements were made at 60 × 60 points at 500 nm intervals, and the area from 0 to 400 cm was measured. -1The integral image obtained shows that the elastic layer is composed of a matrix and multiple domains separated into the matrix. In addition, the matrix and the domains were clearly phase-separated. Next, the Raman spectrum of the matrix and domain parts was measured from the integral image. The measurement was performed with a light source of Nd:YVO4 (wavelength 532 nm), laser intensity of 240 μW, objective lens of 100x, diffraction grating of 300 gr / mm, pinhole diameter of 100 μm, exposure time of 30 seconds, and one integration. From the obtained Raman spectrum, it was confirmed that the matrix contains a structure derived from polycarbonate urethane, and the domain contains a structure derived from polypropylene glycol.
[0074] [Evaluation 2: Measurement of parameters indicating viscoelasticity] First, a first molded body having a cubic shape with one side of 100 μm was obtained in the same manner as in Evaluation 1. A section was prepared from the first molded body using a microtome. Then, a viscoelastic image was measured using a scanning probe microscope (product name: S-Image, manufactured by SII NanoTechnology Inc.). The measurement mode for the viscoelastic image was VE-DFM. In addition, the cantilever used was "SI-DF3" (product name, manufactured by Hitachi High-Tech Science Corporation, spring constant = 1.9 N / m). Furthermore, the scanning frequency was 0.5 Hz. From the obtained viscoelastic images, parameters indicating the viscoelastic term in each observation region were calculated for 10 points each for the matrix and domain, and parameter A (mV) indicating the viscoelastic term of the domain and parameter B (mV) indicating the viscoelastic term of the matrix were obtained from the arithmetic mean values.
[0075] [Evaluation 3: Measurement of micro rubber hardness] First, a sheet-like polyurethane elastomer molded body having a thickness of 2 mm was cut with scissors to obtain a second molded body having a cubic shape with each side measuring 2 mm. The micro rubber hardness of the second molded body was measured using a micro rubber hardness tester (product name: MD-1capa, manufactured by Kobunshi Keiki Co., Ltd.). For the measurement, the second molded body was left in an environment at a temperature of 23°C for 24 hours or more, and the measurement was performed using a measuring device placed in the same environment. In addition, a type A indenter (height 0.50 mm, diameter 0.16 mm, cylindrical, outer diameter 4 mm, inner diameter 1.5 mm) was used, and the measurement mode was peak hold mode.
[0076] [Evaluation 4: Measurement of recovery from deformation] First, a sheet-like polyurethane elastomer molded body having a thickness of 2 mm was cut with scissors to obtain a second molded body having a cubic shape with each side measuring 2 mm. The measurement point was set at approximately the center of any one surface of the second compact, and a nanoindenter (product name: Fischerscope HM2000, manufactured by Fisher Instruments Co., Ltd., a Vickers indenter with a square pyramid shape and a facing angle of 136°) was used to perform an indentation test at a temperature of 23°C. The Vickers indenter was pressed into the second compact at a loading rate of 10 mN / 30 seconds, and the load of 10 mN was maintained for 60 seconds. Thereafter, the load was removed at 10 mN / 30 seconds, and the strain value 5 seconds after the load was removed was measured to measure the recovery from deformation.
[0077] [Evaluation 5: Measurement of abrasion resistance] The wear resistance of the surface in the thickness direction of a sheet-like wear test piece made of polyurethane elastomer, measuring 30 mm in length, 30 mm in width, and 2 mm in thickness, was measured using a ball-on-disk friction and wear tester (product name: HEIDON Type: 20, manufactured by Shinto Chemical Industry Co., Ltd.) in accordance with JIS R1613:2010 under the following conditions (1) to (6). (1) Ball Material: Stainless steel Diameter: 10mm (2) Load: 100g (3)Environment: Temperature 23℃, 50%RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the test specimen is placed: 300 rpm.
[0078] The wear test was carried out as follows. First, the mass of the wear test piece was measured. Next, the wear test piece was fixed with double-sided tape so that the center of the wear test piece was located approximately at the center of the sliding disk of a ball-on-disk friction wear tester (product name: HEIDON Type: 20, manufactured by Shinto Chemical Co., Ltd.). At this time, the surface in the thickness direction of the wear test piece was arranged so as to be in contact with the sliding disk. Next, the indenter made of the above-mentioned ball was pressed against the center of the wear test piece with a load of 100 g, and the wear test piece was rotated and slid for 60 minutes with a sliding circle diameter of 10 mm and a rotation speed of 300 rpm. After 60 minutes, the test piece was stopped, the wear powder and the double-sided tape were removed, and the mass of the test piece was measured. The mass reduction rate (mass%) was calculated from the mass of the test piece before and after the wear test.
[0079] [Example 1] <Preparation example of urethane prepolymer UP1> 31.9 parts by mass of polyol A-1 as a polyether polyol (first polyol) having at least two hydroxyl groups and having a second structure represented by formula (2), 1.0 part by mass of polyisocyanate B-1 as a first polyisocyanate, and 500 ppm of curing catalyst C-1 were mixed and heated at a temperature of 100°C for 4 hours to produce a urethane prepolymer (urethane reactive emulsifier) UP1 having at least two isocyanate groups (step (i)).
[0080] <Production example of urethane elastomer molding No. 1> 92.1 parts by mass of urethane prepolymer UP1, 1.7 parts by mass of B-1, 2.5 parts by mass of B-2, and 3.7 parts by mass of B-2 were mixed and stirred for 2 minutes until homogenized using a self-rotating vacuum stirring degassing mixer (product name: V-mini300, manufactured by EME) at a revolution speed of 1600 rpm (steps (ii) and (iii)). Thus, a polyurethane elastomer forming mixture according to this embodiment was obtained. Next, the polyurethane elastomer forming mixture was preheated to a temperature of 130°C, poured into a mold for producing a 2 mm thick sheet thinly coated with a release agent, and heated at a temperature of 130°C for 2 hours to be cured (step (iii)). Next, the cured product was demolded and post-cured at a temperature of 80°C for 2 days to obtain a polyurethane elastomer molded body No. 1 in a sheet shape with a thickness of 2 mm.
[0081] [Example 2] <Preparation example of urethane prepolymer UP2> The first polyol was 13.5 parts by mass of polyol A-1, the second polyol was 26.9 parts by mass of polyol A-2, and the first polyisocyanate was 4.0 parts by mass of polyol A-3. A polyol having an isocyanate group at its end (first polyether) was synthesized by uniformly mixing the reisocyanate B-1 and 500 ppm of the curing catalyst C-1 and heating at a temperature of 100° C. for 24 hours. Next, 49.4 parts by mass of the polyol A-4 was mixed with the polyol obtained above as a third polyol (first polycarbonate polyol) and heated at a temperature of 100° C. for 4 hours to produce a urethane prepolymer (urethane reactive emulsifier) UP2 (step (i)).
[0082] <Production example of urethane elastomer molding No. 2> Polyurethane elastomer molding No. 2 was obtained in the same manner as in Example 1, except that 93.8 parts by mass of the urethane prepolymer UP2, 2.5 parts by mass of B-1 as the second polyisocyanate, and 3.7 parts by mass of B-2 as the third polyisocyanate were used.
[0083] [Example 3] <Preparation of urethane prepolymer UP3> 35.6 parts by weight of polyol A-2, 4.9 parts by weight of polyisocyanate B-1, and 500 ppm of curing catalyst C-1 was mixed uniformly and heated at 100°C for 24 hours to synthesize a polyol having an isocyanate group at the end. 53.3 parts by mass of polyol A-5 was mixed into this and heated and stirred at 100°C for 4 hours to produce urethane prepolymer UP3.
[0084] <Synthesis of Polyurethane Elastomer No. 3> 93.8 parts by mass of the urethane prepolymer UP3, 2.5 parts by mass of B-2, and 3.7 parts by mass of B-3 were mixed and stirred for 2 minutes until homogenized using a self-rotating vacuum stirring and degassing mixer (product name: V-mini300, manufactured by EME) at a revolution speed of 1600 rpm to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molded body No. 3 was obtained in the same manner as in Example 1, except that the polyurethane elastomer forming mixture was used.
[0085] [Example 4] <Preparation of urethane prepolymer UP4> Polyol having an isocyanate group at the end was synthesized by uniformly mixing 18.0 parts by mass of Polyol A-1, 0.6 parts by mass of Polyisocyanate B-1, and 500 ppm of Curing Catalyst C-1 and heating at a temperature of 100° C. for 24 hours. Polyol having an isocyanate group at the end was mixed with this at 72.1 parts by mass of Polyol A-5 and heated at a temperature of 100° C. for 4 hours to produce Urethane prepolymer UP4.
[0086] <Synthesis of Polyurethane Elastomer No. 4> 93.7 parts by mass of the urethane prepolymer UP4, 3.1 parts by mass of B-1, 2.5 parts by mass of B-2, and 3.7 parts by mass of B-3 were mixed and stirred for 2 minutes until homogeneous using a self-rotating vacuum stirring degassing mixer (product name: V-mini300, manufactured by EME) at a revolution speed of 1600 rpm to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molded body No. 4 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used.
[0087] [Example 5] Except for using Polyol A-6 instead of Polyol A-1, a urethane prepolymer UP5 was prepared in the same manner as in Example 1. In addition, a polyurethane elastomer molded product No. 5 was obtained in the same manner as in Example 1, except for using the urethane prepolymer UP5.
[0088] [Example 6] Except for using Polyol A-7 instead of Polyol A-1, urethane prepolymer UP6 was prepared in the same manner as in Example 1. In addition, except for using urethane prepolymer UP6, polyurethane elastomer molded body No. 6 was obtained in the same manner as in Example 1.
[0089] [Example 7] Except for using Polyol A-8 instead of Polyol A-1, urethane prepolymer UP7 was prepared in the same manner as in Example 1. In addition, a polyurethane elastomer molded product No. 7 was obtained in the same manner as in Example 1, except for using urethane prepolymer UP7.
[0090] [Example 8] <Preparation of urethane prepolymer UP8> 32.5 parts by mass of polyol A-1, 1.0 part by mass of polyisocyanate B-1, and 500 ppm of curing catalyst C-1 were mixed uniformly and heated at a temperature of 100°C for 24 hours to synthesize a polyol having an isocyanate group at the end. 56.8 parts by mass of polyol A-5 were mixed into this and heated at a temperature of 100°C for 4 hours to synthesize a urethane. A prepolymer, UP8, was prepared.
[0091] <Synthesis of Polyurethane Elastomer No. 8> 90.2 parts by mass of the urethane prepolymer UP8 and 0.8 parts by mass of D-1 were mixed. Then, 2.8 parts by mass of B-1, 2.5 parts by mass of B-2, and 3.7 parts by mass of B-3 were mixed, and the mixture was stirred for 2 minutes at a revolution speed of 1600 rpm using a self-revolving vacuum stirring and degassing mixer (product name: V-mini300, manufactured by EME Co., Ltd.) until it became homogeneous, to obtain a polyurethane elastomer forming mixture. Then, a polyurethane elastomer molded body No. 8 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used.
[0092] [Example 9] <Preparation of urethane prepolymer UP9> A polyol having an isocyanate group at the end was synthesized by uniformly mixing 35.9 parts by mass of polyol A-3, 4.1 parts by mass of polyisocyanate B-1, and 500 ppm of curing catalyst C-1 and heating at a temperature of 100° C. for 4 hours. 53.8 parts by mass of polyol A-5 was mixed therein and heated and stirred at a temperature of 100° C. for 4 hours to prepare urethane prepolymer UP9.
[0093] <Synthesis of Polyurethane Elastomer No. 9> 93.8 parts by mass of the urethane prepolymer UP9, 2.5 parts by mass of B-2, and 3.7 parts by mass of B-3 were mixed and stirred for 2 minutes until homogenized using a self-rotating vacuum stirring and degassing mixer (product name: V-mini300, manufactured by EME) at a revolution speed of 1600 rpm to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molded body No. 9 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used.
[0094] [Example 10] <Preparation of urethane prepolymer UP10> A polyol having an isocyanate group at the end was synthesized by uniformly mixing 35.6 parts by mass of polyol A-4, 4.9 parts by mass of polyisocyanate B-1, and 500 ppm of curing catalyst C-1 and heating at a temperature of 100° C. for 4 hours. 53.3 parts by mass of polyol A-5 was mixed therein and heated and stirred at a temperature of 100° C. for 4 hours to produce urethane prepolymer UP10.
[0095] <Synthesis of Polyurethane Elastomer No. 10> 93.8 parts by mass of the urethane prepolymer UP10, 2.5 parts by mass of B-2, and 3.7 parts by mass of B-3 were mixed and stirred for 2 minutes until homogenized using a self-rotating vacuum stirring and degassing mixer (product name: V-mini300, manufactured by EME) at a revolution speed of 1600 rpm to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molded body No. 10 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used.
[0096] [Example 11] <Preparation of urethane prepolymer UP11> A polyol having an isocyanate group at its end was synthesized by uniformly mixing 31.9 parts by mass of polyol A-1, 0.3 parts by mass of polyisocyanate B-1, and 500 ppm of curing catalyst C-1 and heating at a temperature of 100°C for 24 hours. 59.2 parts by mass of polyol A-5 was mixed therein and heated at a temperature of 100°C for 4 hours to produce urethane prepolymer UP11.
[0097] <Synthesis of Polyurethane Elastomer No. 11> 92.1 parts by mass of the urethane prepolymer UP11, 2.4 parts by mass of B-1, 2.5 parts by mass of B-2, and 3.7 parts by mass of B-3 were mixed and stirred for 2 minutes until homogenized using a self-rotating vacuum stirring and degassing mixer (product name: V-mini300, manufactured by EME) at a revolution speed of 1600 rpm to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molded body No. 11 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used.
[0098] [Example 12] <Preparation of urethane prepolymer UP12> A polyol having an isocyanate group at its end was synthesized by uniformly mixing 31.9 parts by mass of polyol A-1, 1.5 parts by mass of polyisocyanate B-1, and 500 ppm of curing catalyst C-1 and heating at a temperature of 100°C for 24 hours. 59.2 parts by mass of polyol A-5 was mixed therein and heated at a temperature of 100°C for 4 hours to produce urethane prepolymer UP12.
[0099] <Synthesis of Polyurethane Elastomer No. 12> 92.1 parts by mass of the urethane prepolymer UP12, 1.2 parts by mass of B-1, 2.5 parts by mass of B-2, and 3.7 parts by mass of B-3 were mixed and stirred for 2 minutes until homogeneous using a self-rotating vacuum stirring and degassing mixer (product name: V-mini300, manufactured by EME) at a revolution speed of 1600 rpm to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molded body No. 12 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used.
[0100] [Comparative Example 1] 87.7 parts by mass of polyol A-5, 4.5 parts by mass of B-1, 3.1 parts by mass of B-2, 4.7 parts by mass of B-3, and 500 ppm of curing catalyst C-1 were mixed, and stirred for 2 minutes until homogeneous at a revolution speed of 1600 rpm using a self-revolving vacuum stirring degassing mixer (product name: V-mini300, manufactured by EME Co., Ltd.), to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molded body No. C1 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used.
[0101] [Comparative Example 2] 35.1 parts by mass of polyol A-2, 52.6 parts by mass of polyol A-9, 4.6 parts by mass of B-1, 3.1 parts by mass of B-2, 4.7 parts by mass of B-3, and 500 ppm of curing catalyst C-1 were mixed, and stirred for 2 minutes until homogeneous using a self-rotating vacuum stirring degassing mixer (product name: V-mini300, manufactured by EME) at a revolution speed of 1600 rpm to obtain a polyurethane elastomer forming mixture. Next, a polyurethane elastomer molding No. C2 was obtained in the same manner as in Example 1, except that this polyurethane elastomer forming mixture was used.
[0102] Table 1 shows the evaluation results of the polyurethane elastomers according to Examples 1 to 12 and Comparative Examples 1 and 2. [Table 1]
[0103] The polyurethane elastomer molding No. 1 according to Example 1 had a significantly reduced hardness compared to the polyurethane elastomer molding No. C1, which was a single polycarbonate obtained in Comparative Example 1. The polyurethane elastomer obtained in Example 1 also had good abrasion resistance and showed a high elastic deformation power (low compression set) comparable to that of silicone elastomers. On the other hand, the polyurethane elastomer molded product No. C2 obtained in Comparative Example 2 had low hardness but low abrasion resistance. Also, compared with Example 1, the recovery from deformation tended to be deteriorated. From the above results, it is clear that the polyurethane elastomer according to the present disclosure exhibits excellent effects of realizing low hardness, good friction characteristics, and low compression set. These effects are believed to be due to the phase separation structure in which the polycarbonate polyurethane is arranged in the matrix and the polyether polyurethane is arranged in the domain.
[0104] The present disclosure relates to the following configurations. [Configuration 1] A polyurethane elastomer having a matrix and a plurality of domains dispersed in the matrix, The relationship between a parameter A indicating the viscoelasticity term of the domain and a parameter B indicating the viscoelasticity term of the matrix, which is measured in a viscoelastic image by a scanning probe microscope of a cut surface parallel to one face of a cubic first molded body made of the polyurethane elastomer and having a side length of 100 μm, is as follows: A <Bであり、 The second molded body made of the polyurethane elastomer has a micro rubber hardness of 20 to 50 degrees at a temperature of 23°C, and In an indentation test using a nanoindenter at a temperature of 23° C. of the second molded body, A Vickers indenter is pressed into the second compact at a loading rate of 10 mN / 30 seconds, and the load of 10 mN is maintained for 60 seconds. After the load is removed, the strain is 1.0 μm or less 5 seconds after the load is removed. A polyurethane elastomer, characterized in that when a ball-on-disk abrasion test is performed on the surface of a sheet-shaped abrasion test piece made of the polyurethane elastomer and having a length of 30 mm, a width of 30 mm, and a thickness of 2 mm in accordance with JIS R1613:2010 under the following conditions (1) to (6), the mass loss rate of the abrasion test piece is 10.0 mass% or less: (1) Ball Material: Stainless steel Diameter: 10mm (2) Load: 100g (3)Environment: Temperature 23℃, 50%RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the test specimen is placed: 300 rpm. [Configuration 2] The polyurethane elastomer is A polyurethane elastomer according to configuration 1, having a first structure represented by the following formula (1) and a second structure represented by the following formula (2), the matrix containing the first structure, and the domain containing the second structure: TIFF2025062409000005.tif26170 (In formula (1), R 1 represents an alkylene group having 3 to 12 carbon atoms. TIFF2025062409000006.tif16170 (In formula (2), R 2 represents an alkylene group having 3 to 6 carbon atoms. [Configuration 3] A polyurethane molding comprising the polyurethane elastomer according to configuration 1 or 2. [Explanation of symbols]
[0105] 3: polyurethane molding, 31: matrix, 32: domain
Claims
1. A polyurethane elastomer having a matrix and a plurality of domains dispersed in the matrix, a relationship between a parameter A indicating a viscoelastic term of the domain and a parameter B indicating a viscoelastic term of the matrix, which is measured in a viscoelastic image obtained by a scanning probe microscope of a cut surface parallel to one face of a cubic first molded article made of the polyurethane elastomer and having one side of 100 μm, is A<B; The second molded body made of the polyurethane elastomer has a micro rubber hardness of 20 to 50 degrees at a temperature of 23°C, and In an indentation test using a nanoindenter at a temperature of 23°C, a Vickers indenter was pressed into the second compact at a loading rate of 10 mN / 30 seconds, the load of 10 mN was maintained for 60 seconds, and then the load was removed. The strain 5 seconds after removal of the load was 1.0 µm or less. A polyurethane elastomer, characterized in that when a ball-on-disk abrasion test is performed on the surface of a sheet-shaped abrasion test piece made of the polyurethane elastomer and having a length of 30 mm, a width of 30 mm, and a thickness of 2 mm in accordance with JIS R1613:2010 under the following conditions (1) to (6), the mass loss rate of the abrasion test piece is 10.0 mass% or less: (1) Ball Material: Stainless steel Diameter: 10mm (2) Load: 100g (3) Environment: Temperature 23℃, 50%RH (4) Time: 60 minutes (5) Sliding circle diameter: 10 mm (6) Rotation speed of the disk on which the test piece is placed: 300 rpm.
2. The polyurethane elastomer is The polyurethane elastomer according to claim 1, comprising a first structure represented by the following formula (1) and a second structure represented by the following formula (2), the matrix containing the first structure, and the domain containing the second structure: (In formula (1), R 1 represents an alkylene group having 3 to 12 carbon atoms. (In formula (2), R 2 represents an alkylene group having 3 to 6 carbon atoms.
3. A polyurethane molding comprising the polyurethane elastomer according to claim 1 or 2.
Citation Information
Patent Citations
Developing blade for electrophotographic device
JP2000029307A
Polyurethane elastomer and method for producing the same
JP2020128461A